Corporate governance and credit spreads on corporate bonds: an empirical study in the context of China*. Issue 1 (2nd January 2017) - Zhou, Hong; Zhou, Chang; Lin, Wanfa; Li, Guoping
Abstract: This article empirically examines the relationship between corporate governance and credit spreads on corporate bonds in the context of China. We find that good corporate governance leads to lower credit spreads on corporate bonds through both improving corporate financial performance and mitigating informational asymmetry between managers and investors. Meanwhile, such an effect is stronger in private-owned enterprises than in state-owned enterprises as the mitigating effect of corporate governance on informational asymmetry is greater in private-owned enterprises than in state-owned enterprises. The findings of this study may be helpful in understanding how corporate bonds are valued in China's corporate bond market and thus help China's firms reduce credit spreads and cost of debt.